Determination of material properties in the Chaboche unified viscoplasticity model - Gong, Y.P.; Hyde, Christopher J.; Sun, W.; Hyde, T.H. (SAGE, 2010)
An experimental programme of cyclic mechanical testing of a 316 stainless steel, at temperatures up to 600°C, under isothermal conditions, for the identification of material constitutive constants, has been carried out using a thermo-mechanical fatigue (TMF) test machine with induction coil heating. The constitutive model adopted is a modified Chaboche unified viscoplasticity model, which can deal with both cyclic effects, such as combined isotropic and kinematic hardening, and rate-dependent effects, associated with viscoplasticity. The characterization of 316 stainless steel is presented and compared with results from cyclic isothermal tests. A least-squares optimization algorithm has been developed and implemented for determining the material constants in order to further improve the general fit of the model to experimental data, using the initially obtained material constants as the starting point in this optimization process. The model predictions using both the initial and optimized material constants are compared to experimental data.